GAMIFICAÇÃO E MOBILIZAÇÃO DE ESTRATÉGIAS INDIVIDUAIS POR APRENDIZES DE LÍNGUA ADICIONAL. - ARAÚJO, Natyara Carvalho (2021)
Inserted at the scope of Applied Linguistics, this research consists of an investigation about the mobilization of individual learning strategies in the acquisition of additional languages through what is called "gamification" - with general objective of identifying the implications of using gamification platforms in mobilizing individual strategies for learning additional languages. To understand this event, we describe the main tools that are found on the platforms and aim to understand the relationship between gamification and the mobilization of individual learning strategies, focusing our investigation especially on the identification of Metacognitive and Affective strategies proposed by Oxford (1990). Thereby, after examinating its objectives, we noted that Oxford research gives emphasis at the learner perspective, wich is the focus of researches in AL in our current context, in addition to considering the existence of several factors that together contribute to learning process. In this perspective, to achieve what was desiderd in our study, we took the Complexity Theory as an epistemological and methodological basis (MORIN, 2011). To understand learning process, a Complex Adaptive System (CAS), we were guided by Larsen-Freeman's studies (1997) about it. In the process of doing this, we describe the main tools found on Kahoot! and Socrative. This study, wich is exploratory, has its content constituted by questionnaires answered by Spanish language learners as an additional language. The questions found in the questionnaire were elaborated and analyzed based on Metacognitive and Affective strategies, that were idealized from the proposal of Oxford (1990), in its inventory. The results we obtained give us an appointment to a significant contribution of the benefits of using games to the mobilization of Metacognitive and Affective strategies, that are linked to the actions of learning and relating to already known content; to discover new things, to monitor and evaluate self learning; of having moments to laugh and relax; of taking risks smartly and to get self-gratification.